2014
DOI: 10.1007/s10566-014-9281-y
|View full text |Cite
|
Sign up to set email alerts
|

Programs for Prevention of Externalizing Problems in Children: Limited Evidence for Effect Beyond 6 Months Post Intervention

Abstract: BackgroundPreventing externalizing problems in children is a major societal concern, and a great number of intervention programs have been developed to this aim. To evaluate their preventive effects, well-controlled trials including follow-up assessments are necessary.MethodsThis is a systematic review of the effect of prevention programs targeting externalizing problems in children. The review covered peer reviewed publications in English, German, French, Spanish and Scandinavian languages. Experimental studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 75 publications
1
28
0
Order By: Relevance
“…Second, since children's disruptive problems often extend from family to peer relationships, several programs add other components that could be implemented with the teachers and the children themselves (both alone or combined). School-based programs resulted eicacious to improve self-regulation and social skills [28]. However, multimodal interventions are necessary when BPT alone is not suicient with children presenting severe disruptive behaviors or comorbid internalizing problems [29].…”
Section: Parenting-based Interventionsmentioning
confidence: 99%
“…Second, since children's disruptive problems often extend from family to peer relationships, several programs add other components that could be implemented with the teachers and the children themselves (both alone or combined). School-based programs resulted eicacious to improve self-regulation and social skills [28]. However, multimodal interventions are necessary when BPT alone is not suicient with children presenting severe disruptive behaviors or comorbid internalizing problems [29].…”
Section: Parenting-based Interventionsmentioning
confidence: 99%
“…Meta-analyses have also revealed larger effect sizes in studies with smaller sample sizes (Farrington and Welsh 2003;Koehler et al 2012), shorter follow-up periods (e.g., Dekovic et al 2011;Lösel and Beelman 2003), and high-risk samples (e.g., Koehler et al 2012), and in studies carried out by program developers (Beelmann and Lösel 2006;Wilson et al 2012). Thus, a recent meta-analysis concluded that there is "an obvious need for more effectiveness studies, carried out by independent researchers" (Smedler et al 2014).…”
mentioning
confidence: 99%
“…In addition, very few methodologically rigorous studies have examined the long-term effectiveness of parent training and social skills programs on delinquency and externalizing behavior (Piquero et al 2009;Smedler et al 2014). In a recent review, Farrington and Welsh (2013) found only 12 studies that had followed participants in the long-term (at least 10 years), had sufficient sample size (at least 50 persons per condition), and included offending as an outcome.…”
mentioning
confidence: 99%
“…Effects sizes within this range are commonly reported in studies evaluating the effects of psychotherapy in children and adolescents [33]. When considering general, selective or indicated prevention programmes for mental health problems smaller effect sizes are reported (small-to-moderate at the best) [34,35]. Nevertheless, assuming our main model to be adequate, our results indicate that interventions reducing mental health problems in adolescence may have the potential to reduce the receipt of medical benefits in young adulthood, and that a mechanism for this estimated effect may be through school completion.…”
Section: Our Findings In Relation To Previous Research and Possible Ementioning
confidence: 99%